Pemetaan Persebaran dan Trendline Kasus Tuberkulosis Di Wilayah Gunungkidul - Hendra; Enjang, Hieronymus Kidung; Kusuma, Oni Noviandi; Rohman, Hendra (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2024)
There has been an increase in TB cases in the Gunungkidul area. TB case findings in 2019, 2020, 2021, 2022, and 2023 were 360, 309, 248, 353, and 528 cases. This study aims to identifies process of collecting health data on TB cases, identifying factors causing TB cases, and mapping distribution of TB cases. Descriptive research with a qualitative approach. The variables are health data on number of TB cases and environmental factors. QGIS 3.34 application was used to create a map of distribution of stunting disease. Process of collecting TB data at Gunungkidul Regency Health Office and health centers has been carried out electronically and online using a web-based information system, namely SITB, but in health centers there are still those who use the TB register book, namely TB 03 to validate data that has been inputted into SITB. The highest TB cases were in Kapanewon Wonosari with 89 cases (18.68%). There are risk factors that influence the incidence of TB in Kapanewon Wonosari and Playen. Population density factor in Wonosari is 1,158.18 per km2, and Playen is 575.93 per km2. Average temperature risk factor is 26.0 °C. Average rainfall risk factor is 244.04 mm. Average altitude factor is 254 meters above sea level. Average humidity factor is 83%. The highest distribution of pulmonary TB cases is in Kepek Village (2.08%), Bleberan and Ngawu Villages, each (1.14%). The highest extrapulmonary TB category is in Karangtengah Village (0.38), and in Bandung and Gading Villages, each (0.19%). The trendline of TB cases in 2019-2023 has increased and decreased every year. Decrease in cases in 2020 (3.00%), in 2021 (3.22%). Increase in cases in 2022 (5.83%), and in 2023 (9.73%). Active case finding and active case monitoring programs need to be carried out by the health office and related stakeholders.